Comprehensive Clinical Management of Moderate Anemia in Third-Trimester Pregnant Women and Delivery Success at PONED Halong Primary Health Center: A Case Analysis in Balangan Regency, South Kalimantan - Laila Azizah (International Medical Journal Corp. Ltd, 2026)
Introduction: Anemia in pregnancy remains a health priority in Indonesia due to its contribution to maternal mortality and stunting (1,2). Decreased hemoglobin (Hb) levels below the normal threshold, especially in the third trimester, increases the risk of fatal obstetric complications (3). This case report aims to analyze the comprehensive clinical management of moderate anemia in a third-trimester pregnant woman until delivery at PONED Halong Primary Health Center, Balangan Regency, South Kalimantan (4). Case: A 22-year-old primigravida (G1P0A0) underwent integrated antenatal care at Halong Primary Health Center . In the first trimester, Hb was normal (13.2 gr/dl) (6). Entering 32-33 weeks of gestation, a drastic Hb decrease to 8.6 gr/dl (moderate anemia) was observed, accompanied by proteinuria +1 and random blood glucose (RBG) of 163 mg/dl (7). Interventions included escalating Iron Supplement Tablets (TTD) to 3x1 tablet per day combined with Multiple Micronutrient Supplements (MMS) 1x1 tablet per day and Calcium Lactate 2x500 mg per day (8). At 38 weeks gestation, the patient had a spontaneous delivery at the PONED unit (9). The infant weighed 3495 grams, but the mother experienced a second-degree perineal laceration requiring suturing (10). Discussion: The sharp Hb decline indicates failure of physiological compensation and depletion of maternal iron stores in the third trimester (11). MMS proved superior to standard iron-folate supplementation, reflected in optimal birth weight despite maternal anemia (12). Proteinuria +1 without hypertension likely relates to anemia-induced renal effects or asymptomatic urinary tract infection (13). RBG of 163 mg/dl indicates mild gestational diabetes mellitus, contributing to large birth weight through fetal hyperinsulinemia (14). Active management of the third and fourth stages of labor at PONED was key to preventing massive hemorrhage (15). Conclusion: Aggressive management of moderate anemia in the third trimester through multidimensional micronutrient supplementation significantly improves delivery outcomes (16). Synergy between early detection in antenatal care and PONED unit preparedness is vital to reduce maternal morbidity (17). Strengthening serial laboratory screening and education on supplement adherence is recommended (18).